2009
DOI: 10.1038/tpj.2009.39
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating the pharmacogenetic effects of angiotensin-converting enzyme inhibitors on long-term prognosis of diastolic heart failure

Abstract: The objective of this study was to evaluate the effects of angiotensin-converting enzyme (ACE) inhibitors and pharmacogenetic interaction on the survival of the patients with diastolic heart failure (DHF). A total of 285 subjects with DHF confirmed by echocardiography were recruited in the period between 1995 and 2003. Baseline characteristics (age, sex, prior history, medication, and echocardiographic findings) and genetic polymorphisms (ACE gene insertion/ deletion (I/D) polymorphism; T174M, M235T, G-6A, A-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 32 publications
1
20
1
Order By: Relevance
“…Although ACE inhibitors work on multiple pathways in the RAAS, single SNP analysis may generate less useful data and fail to clarify the clinical significance of RAAS gene variation for the use of ACE inhibitors. The genetic influence of RAS gene polymorphisms on cardiovascular disease, especially on the susceptibility and progression of CAD or heart failure, has been studied widely [17,30]. Recently, the PERindopril GENEtic (PERGENE) study examined the genetic determinants of the treatment benefits of ACE inhibitor therapy and concluded that genetic variants modifying the treatment effect of perindopril were particularly located in the AGT1R and bradykinin 1 receptor genes [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ACE inhibitors work on multiple pathways in the RAAS, single SNP analysis may generate less useful data and fail to clarify the clinical significance of RAAS gene variation for the use of ACE inhibitors. The genetic influence of RAS gene polymorphisms on cardiovascular disease, especially on the susceptibility and progression of CAD or heart failure, has been studied widely [17,30]. Recently, the PERindopril GENEtic (PERGENE) study examined the genetic determinants of the treatment benefits of ACE inhibitor therapy and concluded that genetic variants modifying the treatment effect of perindopril were particularly located in the AGT1R and bradykinin 1 receptor genes [30].…”
Section: Discussionmentioning
confidence: 99%
“…An insertion/ deletion (I/D) polymorphism in the ACE gene on chromosome 17 has been found to be a major determinant of the ACE serum level, which may influence the extent of vasoconstriction [11]. This polymorphism on chromosome 17 also predicts the clinical outcome in cardiovascular disease, including CAD, myocardial infarction, left ventricular hypertrophy, atrial fibrillation, diastolic heart failure, and hypertension [12][13][14][15][16][17]. It is unclear whether this genetic variation modifies the clinical efficacy of ACE inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is well known that angiotensin-converting enzyme (ACE) I/D gene D allele was associated with higher overall mortality as compared with the I allele in HF patients and that the effect could be modified by ACE inhibitors' given (Kolder et al, 2012). Additionally, ACE DD and angiotensin-1-receptor 1166 CC genotypes may synergistically increase the predisposition to HFpEF (Wu et al, 2010).…”
Section: Genetic Biomarkersmentioning
confidence: 99%
“…Indeed, some early studies have reported interested results with respect to genetic precursors of HFpEF and HFrEF [16][17][18][19][20][21][22]. As biomarkers particularly used to scrutiny single nucleotide polymorphisms (SNPs) of genes encoding enzymes related to oxidative stress [16], genotype of guanine nucleotide-binding proteins (G-proteins) β-3 subunit (GNB3) [17], transcription factor Islet-1 gene [18], troponin T [19], CYP2D6 polymorphism [20], cardiac myosin binding protein-C mutations [19], renin-angiotensin-aldosterone system polymorphism [21] etc.…”
Section: Introductionmentioning
confidence: 99%
“…As biomarkers particularly used to scrutiny single nucleotide polymorphisms (SNPs) of genes encoding enzymes related to oxidative stress [16], genotype of guanine nucleotide-binding proteins (G-proteins) β-3 subunit (GNB3) [17], transcription factor Islet-1 gene [18], troponin T [19], CYP2D6 polymorphism [20], cardiac myosin binding protein-C mutations [19], renin-angiotensin-aldosterone system polymorphism [21] etc. Indeed, it is well known that angiotensin-converting enzyme (ACE) I/D gene D allele was associated with higher overall mortality as compared with the I allele in HF patients and that the effect could be modified by ACE inhibitors' given [22]. Additionally, ACE DD and angiotensin-1-receptor 1166 CC genotypes may synergistically increase the predisposition to HFpEF [23].…”
Section: Introductionmentioning
confidence: 99%